Marine debris ingestion by Southern Giant Petrels and its potential relationships with fisheries in the Southern Atlantic Ocean - Copello, Sofía; Quintana, Flavio Roberto (Marine Pollution Bulletin)
The quantity of litter in the worlds oceans has been steadily increasing over the years. Within the Southern Ocean, the amount of debris increased 100-fold during the early 1990s (Barnes, 2002) and fisheries appear to be the greatest single source (Burton and Riddle, 2001). The composition of floating debris has become dominated by anthropogenic plastics and polystyrenes, metals and glass (Burton and Riddle, 2001). Seabirds ingest floating plastics and other foreign matter while feeding on the surface of the ocean (Ryan, 1987). The prevalence of plastic ingestion by seabirds has increased and is well documented in many families of Procellariiformes (Bourne and Imber, 1982; Ryan et al., 1988; Kinan and Cousins, 2000). The Southern Giant Petrel (Macronectes giganteus) is a wide ranging procellariform which breeds in the coasts of Patagonia and forages throughout the Argentine continental shelf (Quintana and Dell Arciprete, 2002), and which often interacts with fisheries activities. Little is known about their diet and their extent of marine debris ingestion. To date, there is only one published reference of ingestion of marine debris by Southern Giant Petrel from Marion island at the Subantarctic Ocean (Nel and Nel, 1999). Here we evaluate the presence of marine debris in the diet of Southern Giant Petrels chicks at a colony on the Patagonian coast. Fil: Copello, Sofía. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Quintana, Flavio Roberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina